Foundations for desgning user-centered systems: what system designers need to know about people - Ritter, Frank E.; Baxter, Gordon D.; Churchill, Elizabeth F.
Interactive technologies pervade every aspect of modern life. Web sites, mobile devices, household gadgets, automotive controls, aircraft flight decks; everywhere you look, people are interacting with technologies. These interactions are governed by a combination of: the users' capabilities; the things the users are trying to do; and the context in which they are trying to do them. All of these factors have to be appropriately considered during design if you want your technology to provide your users with a good experience. Foundations for Designing User-Centered Systems introduces the fundamental human capabilities and characteristics that influence how people use interactive technologies. Organized into four main areas-anthropometrics, behaviour, cognition and social factors-it covers basic research and considers the practical implications of that research on system design. Applying what you learn from this book will help you to design interactive systems that are more usable, more useful and more effective. The authors have deliberately developed Foundations for Designing User-Centered Systems to appeal to system designers and developers, as well as to students who are taking courses in system design and HCI. The book reflects the authors' backgrounds in computer science, cognitive science, psychology and human factors. The material in the book is based on their collective experience which adds up to almost 90 years of working in academia and both with, and within, industry; covering domains that include aviation, consumer Internet, defense, eCommerce, enterprise system design, health care, and industrial process control. The lack of accessible and comprehensive material on human factors for software engineers has been an important barrier to more widespread acceptance of a human-centred approach to systems design. This book has broken down that barrier and I can thoroughly recommend it to all engineers. Ian Sommerville, University of St Andrews, UK As a chief architect for large programmes, this book has given me access to a variety of new techniques and an extended vocabulary that I look forward to introducing my design teams to. Richard Hopkins, IBM, UK Even if only a proportion of designers and users read this book we will be so much better off. If it gets the circulation it deserves it could change our world - and that very much for the better. Peter Hancock, University of Central Florida, USA